Proposed study of Information Communication Technology (ICT) works interface strategy for construction-based project - Md Taib, Mohd Azahani; Mohd Nawi, Mohd Nasrun; Omar, Mohd Faizal (AENSI Journals, 2014)
The purpose of this research is to formulate and develop an ICT works interface strategy for construction-based project in construction industry.ICT works interface framework will be developed based on requirement engineering approach and work interface mapping.One of the major issues in delivery of ICT works is unavailability of ICT interface strategy and methodology to be referred by ICT contractors or system integrators involved in construction-based project.The problem arise when interfacing processes are not well understood and coordinated properly especially in large scale construction project which has complex tasks of engineering integration.This research is an “action research” where the root of problem is originated from the workplace area of the researcher.This research will identify the common practice of work integration between ICT and engineering, interfacing processes and type of ICT works involved in a construction-based project experienced and managed by KLIA Consultancy Services Sdn Bhd (KLIACS).Qualitative method will be applied where two case studies will be conducted in order to gain information of ICT plan and method used during the project implementation. The expected result of this research would be the creation of an ICT work interface strategy which able to provide interface planning and framework for delivering ICT works involved in construction-based project.It is anticipated that the result would be able to contribute to the improvement of the ICT works interface and project integration as well as the enhancement of the project quality management system of KLIACS.It would also become part of references for the company to manage ICT works for its entire construction-based project. The result is also expected to benefit the government, ICT players